(untitled) (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional De Tecnología, Ciencia Y Sociedad, 2022)
We share experiences in two related fields: •Sustainability “4R” (“Reuse, Repair, Recycle, Reduce”) recoveringPersonal Computers (PCs) without official maintenance, prolonging theiruseful life and avoiding unnecessary purchases. •Teaching of Degree subjects through free software applications on themost powerful recovered PCs such as LAMP servers (Linux-Apache-MySQL-PHP). Many subjects in the Degree require hands-on experience with real working environment applications. High quality and didactic properties are features of many free software applications. With no acquisition cost –and the possibility of running them on recycled PCs– these applicationsare accessible to both, teachers and students.